GAFOTER : GANITRUS OIL FOR FATTY ACID METHYL ESTER SEBAGAI UPAYA GREEN ENERGY - Mahdalina Mursilati; Kharisma Dian Nurani; Ganesha Ucha Faradhita (Universitas Tidar, 2020)
Ganitri (Elaeocarpus ganitrus) is one of the annual plants that grows in Indonesia, especially in Java. Ganitri seeds have not been fully utilized. Indonesian ganitri seeds are not widely known for their chemical content, so they are only used as jewelry and trade. This research was conducted to determine the potential of ganitri seeds as biodiesel feedstock. The research method used is the method of sochletation and maceration. The results showed that the effective content of ganitri seed oil was obtained by the sochletation method. The level of FFA (Free Fatty Acid) of ganitri seed oil is 2.8%, so preliminary action needs to be taken, namely the esterification process in the process of making biodiesel. From the results of the research conducted, ganitri seed oil can be used as raw material for making biodiesel but is less effective for mass production.